PENGEMBANGAN MEDIA PEMBELAJARAN PANCANIMASI MATERI SIMBOL, SILA PANCASILA DAN LAMBANG GARUDA PANCASILA KELAS 1 SD LABORATORIUM - Cahyani, Rahma; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of Learning media in the Laboratory Elementary School is considered less effective, and student learning outcomes remain low based on observations and interview with first-grade teacher. This study aims to: 1) determain the validity, 2) practicially, and 3) effectiveness of the PANCANIMASI media. The research method used is Research and Development or R&D, applying the ADDIE model approach. The steps in this research include analysis, design, development, implementation, and evaluation. The requireddata were collected through expert validation questionnaires (media and content experts), teacher and student response questionnaires, as well as student test results. Base on validation questionnaires, the media recieved scores of 87,5% and 93,3%, indicating that the media is highly valid. Teacher and student responses showed practicaity percentages of 96%, 95,71% in the limited trial and 92,85% in the wider trial, suggesting that the developed media is highly practical for classroom use. The results of the Classical Learning Mastery (KBK) show a 100% mastery rate with average scores of 91,6% in the limited trial and 90,7% in the wider trial. Thus, the media can be considered effective in improving student learning outcomes on the topics of symbols, Pancasila principles, and the Garuda Pancasila emblem for first-grade at the Laboratory Elementary School.